Success factors and change management in Malaysian Institutions of Higher Learning (IHL) - Safitri, Cutifa; Faisal, Ammy Amelia; Ahmad Dahlan, Abdul Rahman (International Journal of Science and Research, 2013)
More and more researchers and academic practitioners in Malaysia turn their interest into learning how the Institutions of Higher Learning (IHL) accommodate their success factors in change management. IHL, administered under the Ministry of Higher Education (MOHE), is one of the most important institutions that requires a successful strategic plan, reducing failure in projects and good inter-institutional relationships. IHL, that carries education through its citizens in the country, must have state-of-the-art strategic plans and 'bulletproof' change management practices. The failure in this institution means failure of accommodating education, dynamic relationship between students, and affecting mentality, monetary and not to mention good will in an educational institution itself. However, a shortcoming within the leadership, people and management caused by private or public institutions can be lessons learned for a better nation. Thus, this study carries to examine how project success and change management is being applied in Malaysia's IHL. This research aims to introduce how project change management in IHL is being applied and the measures that are being used in the Information Technology environment. This paper method uses the three value-driven relationship as a framework throughout data collection and analysis. The value-driven relationships are capable to offer optimum determination of strong framework used in business value. By using this approach, the expected outcome of this study is to show a stronger picture of managing project change management in IHL in Malaysia.